Marque Levy et marque Musso ou la sortie ritualisée de romans français contemporains - Knapik, Adam (Romanica Silesiana)
Marc Levy and Guillaume Musso are two contemporary French representatives of popular literature, who distinguish themselves among other authors by their significant presence in the media, for example social networks such as Facebook. Their fan pages allow them to conduct a promotional campaign of the novels coming out every year. Many elements of the Facebook promotional activity are repeated with every new novel release. In this text, we are analysing the content of these two writers’ fan pages from the period 2011—2013, including the book covers from these years, in order to answer how and why Levy and Musso resort to the method of ritualization based on the same behaviours, information or communication duplicated every year at the same time. References to the term “branding”, to the sociology of literature and also to contemporary studies about writers’ network presence help us in developing significantly this interdisciplinary analysis. Key words: Marc Levy, Guillaume Musso, ritualization, popular literature, French popular contemporary novels, Facebook, branding, mark